2020
DOI: 10.1186/s12890-020-01329-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between sestrin2 expression and airway remodeling in COPD

Abstract: Background Airway remodeling is a major pathological characteristic of chronic obstructive pulmonary disease (COPD), and has been shown to be associated with oxidative stress. Sestrin2 has recently drawn attention as an important antioxidant protein. However, the underlying correlation between sestrin2 and airway remodeling in COPD has yet to be clarified. Methods A total of 124 subjects were enrolled in this study, including 62 control subjects and 62 COPD patients. The pathological changes in airway tissues… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Cigarette smoke exposure offers the closest environment to the disease in humans, and this method has been successfully adopted in the construction of various animal COPD models [ 12 ]. In the evaluation of animal COPD models, pulmonary histopathological examination can determine whether the pathological changes in the small airways and pulmonary parenchyma are consistent with the typical changes seen in COPD [ 13 ]. In the present experiment, the COPD rat model was constructed by fumigation and intratracheal injection of LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke exposure offers the closest environment to the disease in humans, and this method has been successfully adopted in the construction of various animal COPD models [ 12 ]. In the evaluation of animal COPD models, pulmonary histopathological examination can determine whether the pathological changes in the small airways and pulmonary parenchyma are consistent with the typical changes seen in COPD [ 13 ]. In the present experiment, the COPD rat model was constructed by fumigation and intratracheal injection of LPS.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that both serum level and tissue expression of Sestrin2 are higher in patients with COPD. Furthermore, a positive correlation was found between serum Sestrin2 level and serum MMP9 level or airway remodeling in chest CT-scan [191]. Similarly, it was uncovered that patients with asthma have higher plasma levels of Sestrin2.…”
Section: Respiratory Diseasesmentioning
confidence: 84%
“…Experienced nurses took blood samples from septic shock patients within 24 hours of admission and from healthy controls during a physical examination. Blood samples were obtained from research participants in procoagulant tubes, and the supernatant was centrifuged after 20 minutes at 1000 rpm as the sample for testing [ 15 ]. Serum samples were kept at a temperature of minus 80 degrees Celsius (blood collection to serum storage time not exceeding 45 minutes, which can be stored for 2 months for backup) for later use.…”
Section: Methodsmentioning
confidence: 99%